Ocular status of a sample of public bus drivers in the Klang Valley - Sharanjeet-Kaur,; Hazemie K.K.Z.,; Abd Manan F., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2003)
Objective: To determine the distance and near visual acuity (VA), near point of accommodation (NPA) and convergence V C ) , distance and near phoria, stereopsis and colour vision of a sample of public bus drivers in the Klang Valley. Methodology: A total of 52 bus drivers from a randomly chosen public bus operating company in the Klang Valley were examined. The optometric examinations carried out were measurement of visual acuity for distance using the Snellan chart, measurement of near acuity using a reading chart, measurement of near point of accommodation and convergence using the R4F rule, measurement of distance phoria using the Maddox cross, measurement of near phoria using the Maddox wing, measurement of stereopsis using the W O and assessment of colour vision using the Zshihara plates, SPP2 plates, D1 5 panel and FM1 00 Hue test. Results: The study showed that 100% of the drivers had distance VA better than 6/12. For near VA, 57.7% of drivers could read N6 or better while 26.9% and 15.4% could only read NI0 or N12 respectively. Their mean NPA and NPC were 19.00 f 8.26 cm and 13.00 2 7.30 cm respectively. Phoria testing revealed that the bus drivers had a mean exophoria for distance of 0.33 f 0.18 prism diopters and a mean right hypophoria for distance of 0.06 f 0.22 prism diopters. For near vision, these drivers had a mean exophoria of 0.69 f 2.59prism diopters and a mean right hyperphoria of 0.04 -+ 0.20prism diopters. Stereoacuity test found that 65.4% of the bus drivers had stereopsis in the normal range, that is 30 to 60 second of arc. Colour vision tests showed that percentage of subjects that passed were high, that is 92.3% using the Zshihara plates, 61.5% using the SPPZ plates, 53.8% using D-15 and 53.8% using the FM 100-Hues tests. Drivers that failed SPP2 plates had tritan types of defects (30.8%) and mixed type of defects (7.7%). Testing colour vision with D-15 test showed that 19.2% of the bus drivers had tritan type of defects, 15.4% had non-polar arrangement type of defects whereas 7.7% were protans and 3.8% were deutans. FM 100-Hue testing revealed that 19.2% of these bus drivers had tritan type of defects, 23.1 % had non-polar arrangement type of defects whereas 3.8% were protans. Square root of the total error score (VfrES) were calculatedffom the FM 100-Hue test. The &ES of the bus drivers in this study was calculated to be 9.47 f 4.68 whereas the &ES of normals subjects in the same age range collected by Verriest et al. (1982) is 8.23 f 2.44. There was no statistically significant dzfference between-the &ES of bus drivers in this study and the ETS normal subjects in the same age range. Conclusion: It can be concluded that the visual status of the bus drivers is good but the colour vision status is not very satisfactory.